2019
DOI: 10.3390/pathogens8040166
|View full text |Cite
|
Sign up to set email alerts
|

Genome Mining and Comparative Pathogenomic Analysis of An Endemic Methicillin-Resistant Staphylococcus Aureus (MRSA) Clone, ST612-CC8-t1257-SCCmec_IVd(2B), Isolated in South Africa

Abstract: This study undertook genome mining and comparative genomics to gain genetic insights into the dominance of the methicillin-resistant Staphylococcus aureus (MRSA) endemic clone ST612-CC8-t1257-SCCmec_IVd(2B), obtained from the poultry food chain in South Africa. Functional annotation of the genome revealed a vast array of similar central metabolic, cellular and biochemical networks within the endemic clone crucial for its survival in the microbial community. In-silico analysis of the clone revealed the possessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 111 publications
0
9
0
Order By: Relevance
“…Multiple introductions of ST612 was observed in Western Australia in both human and equine reservoirs [ 47 ]. ST612 was also recently observed in the clone ST612-CC8-t1257-SCCmec_IVd(2B) obtained from the poultry food chain in South Africa [ 48 ]. In addition to the studies mentioned above, the Brazilian/Hungarian clone ST239-III-t037 was commonly found over a 15 year period in a study in China beginning in 1994 [ 40 ].…”
Section: Discussionmentioning
confidence: 70%
“…Multiple introductions of ST612 was observed in Western Australia in both human and equine reservoirs [ 47 ]. ST612 was also recently observed in the clone ST612-CC8-t1257-SCCmec_IVd(2B) obtained from the poultry food chain in South Africa [ 48 ]. In addition to the studies mentioned above, the Brazilian/Hungarian clone ST239-III-t037 was commonly found over a 15 year period in a study in China beginning in 1994 [ 40 ].…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, tree analyses coupled with metadata insights depicted the diversity among the E. coli isolates with no correlation with their meat sources and sampling areas. The use of visual analytics increases confidence during molecular investigation of pathogens [ 65 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…These virulence determinants were predominantly made up of adherence determinants which aid in the complement-independent attachment to host mammalian cells [32]. H2730R possessed toxins to induce cell membrane damage, trigger cytokine formation, and reduce or kill neutrophils [33]. Interestingly, the strain also harbored the ibeB and pgaC genes, which contribute to invasion, biofilm formation, and adhesion to eukaryotic host cells.…”
Section: Discussionmentioning
confidence: 99%